x-4+1=-3-x

Simple and best practice solution for x-4+1=-3-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-4+1=-3-x equation:


Simplifying
x + -4 + 1 = -3 + -1x

Reorder the terms:
-4 + 1 + x = -3 + -1x

Combine like terms: -4 + 1 = -3
-3 + x = -3 + -1x

Add '3' to each side of the equation.
-3 + 3 + x = -3 + 3 + -1x

Combine like terms: -3 + 3 = 0
0 + x = -3 + 3 + -1x
x = -3 + 3 + -1x

Combine like terms: -3 + 3 = 0
x = 0 + -1x
x = -1x

Solving
x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
x + x = -1x + x

Combine like terms: x + x = 2x
2x = -1x + x

Combine like terms: -1x + x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 3+3u=18 | | 250+150x=300y | | 10-3p+4p=20 | | F(4)=-3(-9)+10 | | 200+.25n=325 | | x+3x-2=18 | | 6m-2m= | | 9x+15=8x+4 | | 7=-5+4x | | (2x+50)=(5x+5) | | 56+x+85+42=180 | | 4x-5=102 | | 8-6(m-3)+4=4(m+7) | | 6x-1+11=53 | | x+-20=-16 | | F(3)=4(-5)-7 | | 9t^2-72t-54=0 | | (6x+5)(3x-4)=(2x+3)(9x-7) | | 3x-2y+5z=13 | | a^2+(a^2+4)=100 | | 3y-1+40=5x | | -6x+-18=-12 | | -(6n-4)=-7(2n+3)+3n | | 13x+7x=106 | | 3(X*5)=120 | | 13x+7s=106 | | x^2+20=8 | | 2x+2=92 | | 12/x=2/50 | | -4+f=18 | | 3x-24+15=-18 | | 50+105x=14.75x |

Equations solver categories